SOME NEW RECORDS OF MARINE ALGAE FROM VIETNAM - Hau, Le Nhu; Ly, Bui Minh; Huynh, Tran Van; Trung, Vo Thanh (Vietnam Journal of Marine Science and Technology, 2015)
In May 2013, a scientific expedition was organized by the Vietnam Academy of Science and Technology and the Far Eastern Branch of the Russian Academy of Sciences (FEBRAS) in the frame of the VAST-FEBRAS International collaboration program. The expedition went along the coast of Vietnam from Quang Ninh to Kien Giang. The objective was to collect natural resources for investigation of the biological and biochemical diversity of the territorial waters of the Socialist Republic of Vietnam. Among the collected algae, six taxa are new records for the Vietnam algal flora. They are the red algae Titanophora pikeana (Dickie) Feldmann from Cu Lao Xanh Island, Laurencia natalensis Kylin from Tho Chu Island, and Coelothrix irregularis (Harvey) Børgesen from Con Dao Island, and the green algae Caulerpa oligophylla  Montagne, Caulerpa andamanensis (Taylor, W. R., 1975) Draisma, Prudhomme et Sauvage from Phu Quy Island and Caulerpa falcifolia Harvey & Bailey from Ly Son Island. The seaweed flora of Vietnam now counts 833 marine algal taxa, including 415 Rhodophyta, 147 Phaeophyceae, 183 Chlorophyta and 88  Cyanobacteria.